Visualizing shipbuilding features through textual evidence: the case of the 19th century Aegean brigs - Demesticha, Stella; Evripidou, Andri (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Brig was the predominant ship type constructed on the island of Syros, Greece, the main shipbuilding centre of the Aegean, during the 19th century. To gain insights into the Mediterranean shipbuilding technology of the period, a project was conducted aiming to retrieve and analyse shipbuilding data from contracts concerning brigs built between 1832 and 1857 in Ermoupoli’s shipyards. The information was used for the creation of a digital model. This research highlighted the challenges encountered in examining archival sources, as well as their potential as unique resources for understanding the technology and anthropology of shipbuilding.